The Bidirectional Social-Cognitive Mechanisms of the Social-Attention Symptoms of Autism - Mundy, Peter; Bullen, Jenifer (Frontiers in Psychiatry, 2022)
The social attention symptoms of ASD begin to be apparent in the 6th to 12th month of development in infancy, and likely reflect important elements of its neurodevelopmental and neurogenetic endophenotype. This paper examines recent theory and research that has advanced new hypothesis about the mechanisms that contribute to these early symptoms. An axiom of recent theory on social attention is that the development of social attention involves bidirectional social processes. Indeed, recent research suggests that the social attention symptoms of autism reflect the early atypical development of the experience or perception of being the object of attention of others, as well as differences in the development of social orienting or the allocation of attention to other people. The bidirectional hypothesis is also consistent the proposal that infant social attention symptoms are a unique dimension of the phenotype of ASD that reflect domain specific aspects of attention development that cannot be fully explained in terms of domain general aspects of attention development. Finally, both developmental and neurocognitive studies support the hypothesis that social attention symptoms in infancy, and social cognitive symptoms in childhood and adulthood constitute a developmentally continuous axis of symptom presentation in ASD. This new conceptualization of the social attention symptoms of ASD has implications for conceptualizing diagnostic dimensions, the measurement of social attention, social attention treatment and future research on the developmental mechanisms of ASD.